Strength and variability of the Oligocene Southern Ocean surface temperature gradient - Frida S. Hoem; Isabel Sauermilch; Adam K. Aleksinski; Matthew Huber; Francien Peterse; Francesca Sangiorgi; Peter K. Bijl (Communications Earth & Environment, 2022)
The deepening of the Drake Passage cooled Antarctic coasts and increased the temperature gradient between Australia and Antarctica which ultimately enhanced thermal isolation of the Antarctic Ice sheet, according to biomarker derived temperature records and simulation output.